(untitled) (Journal of Pharmaceutical Negative Results, 2023)
A systematic review was carried out on the production and publication of research papers on the study of Scanning Electron Microscopy Techniques (SEM) and Transmission (TEM) under the PRISMA approach (Preferred Reporting Items for Systematic reviews and Meta-Analyses). The purpose of the analysis proposed in the present document was to determine the main characteristics of the publications registered in the Scopus and Wos databases during the year and their scope in the study of the proposed variables, achieving the identification of 15 publications in total. Thanks to this first identification, it was possible to refine the results through the keywords entered in the search button of both platforms, which were SEM, TEM, BENTH reaching a total of 11 documents, already excluding duplicates and those that did not meet the analysis criteria. The identified scientific publications were analyzed hoping to know the main characteristics within the execution of research projects concerning the study of the use of scanning electron microscopic (SEM) and transmission electron microscopic (TEM) techniques in the internal components of the nodules of the endemic legume Clitoria brachystegia (Benth.).